Review and update of paramphistomosis - Sanabria, Rodrigo Eduardo Fabrizio (2008)
Despite records of ruminal paramphistomes in Argentina dating back to the beginning of the XX century, in the last decade cases have increased in number with evidence of spreading to new geographical areas. This fact led us to carry out some studies in the last few years in order to enhance the poor availability of reports in South America, some of which are actually performed in our group. This paper reviews the characteristics of the life cycles and some aspects of the disease both at world and local level, and updates the latest paramphistome reports in domestic ruminants of Argentina.